2010
DOI: 10.1007/s00436-010-2002-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of clomipramine and allopurinol for the treatment of the experimental infection with Trypanosoma cruzi

Abstract: We have previously shown that clomipramine and allopurinol used separately are effective in preventing chronic chagasic cardiomyopathy. The aim of the present study was to evaluate the effect of the association of clomipramine (Clo--5 mg/kg/day/90 days) and allopurinol (Allo--5, 10, or 15 mg/kg/day/90 days) for the treatment of experimental Chagas disease in the acute stage. Treatment effectiveness was evaluated through parasitemia, survival, electrocardiography, serology, and cardiac histopathology. Groups tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…For this reason, in the last 2 decades, new approaches focusing on parasite-specific targets to address this illness have been studied, and different strategies with the overall aim of finding a cure for Chagas disease are under investigation. In particular, we focused on trypanothione reductase, a specific enzyme of T. cruzi that performs vital functions in the parasite, and on CMP, which presents inhibitory effects on trypanothione reductase activity (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, in the last 2 decades, new approaches focusing on parasite-specific targets to address this illness have been studied, and different strategies with the overall aim of finding a cure for Chagas disease are under investigation. In particular, we focused on trypanothione reductase, a specific enzyme of T. cruzi that performs vital functions in the parasite, and on CMP, which presents inhibitory effects on trypanothione reductase activity (40).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, BZ produces free radicals and/or electrophilic metabolites and induces oxidative stress in the parasite (17). On the other hand, CMP inhibits trypanothione reductase (22,40,43), an essential component of the antioxidant defenses of T. cruzi. As a consequence, it is plausible to think that these mechanisms would work together against the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…This approach might improve the efficacy of treatment (by generating additive or synergistic effects on different pharmacological targets) and decrease the likelihood of drug resistance and toxic effects (by reducing the drug dosages or treatment durations used). Several associations of two drugs inducing limited improvements in mice [15][16][17][18][19][20] or in patients [21] have been tested. However, as far as we know, no experimental studies or clinical trials combining the already patented drugs available on the market (BZL, NFX, POS and AMB) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Even though it is widely prescribed, there are major concerns related with the frequency of serious side effects, including allergic dermatitis, gastrointestinal intolerance, anorexia, weight loss and sleeping disorders [ 6 ]. Several authors have reported different treatments in experimental murine model using lower doses of BNZ alone or combined with other drugs, to improve treatment efficacy and decrease adverse side effects [ 7 , 8 , 9 ]. Despite the fact that these reports have shown certain benefits in terms of survival rate and lower parasitemia, there is an urgent need to develop novel therapeutic alternatives using low doses of BNZ for further successful clinical translation.…”
Section: Introductionmentioning
confidence: 99%